Dracorhodin perchlorate protects pancreatic β‐cells against glucotoxicity‐ or lipotoxicity‐induced dysfunction and apoptosis in vitro and in vivo. (14th August 2019) - Liu, Lei; Liang, Chen; Mei, Pucheng; Zhu, Hong; Hou, Meiling; Yu, Chunlei; Song, Zhenbo; Bao, Yongli; Huang, Yanxin; Yi, Jingwen; Wang, Shuyue; Wu, Yin; et al.
Abstract : Glucotoxicity or lipotoxicity leads to hyperglycemia and insulin secretion deficiency, which are important causes for the onset of type 2 diabetes mellitus (T2DM). Thus, the restoration of β‐cell function is a long‐sought goal in diabetes research. Previous studies have implicated pancreatic and duodenal homeobox 1 gene ( Pdx1 ) in β‐cell function and insulin secretion. In this study, we established a Pdx1 promoter‐dependent luciferase system and identified the natural compound dracorhodin perchlorate (DP) as an effective promotor of Pdx1 expression. We further demonstrated that DP could significantly inhibit β‐cell apoptosis induced by 33 mm glucose or 200 μm palmitate by interfering with endoplasmic reticulum stress and mitochondrial pathways and enhance insulin secretion as well. These effects were associated with enhanced activities of Erk1/2, which in turn promoted Pdx1 expression and increased the ratio of Bcl2/Bax, since inhibition of the Erk1/2 pathway abolished the DP‐induced expression of Pdx1 and suppression of apoptosis. In addition, our in vivo results in diabetic mice indicated that DP treatment lowered blood glucose, raised insulin levels, enhanced Pdx1 expression and increased islet size and number in the pancreas of diabetic mice. Our findings suggest that Pdx1 is a potential target molecule of DP in the treatment of T2DM via the inhibition of glucotoxicity‐ or lipotoxicity‐ induced β‐cell apoptosis and the attenuation of insulin secretion dysfunction. Abstract : In vitro, dracorhodin perchlorate protects insulin‐secreting INS‐1 cells against glucotoxicity‐ or lipotoxicity‐induced dysfunction and apoptosis by promoting Pdx1 expression via the Erk signaling pathways. In diabetic mice, the compound exerts therapeutic effects by lowering blood glucose, raising insulin levels, enhancing Pdx1 expression, and increasing islet size and number in the pancreas. These findings suggest that dracorhodin perchlorate can be incorporated into a new beneficial adjuvant therapy in patients with type 2 diabetes mellitus.